A necrotic tonsillar lesion: An unusual presentation of disseminated histoplasmosis. (2017) - Keen, Christopher; Lee, Hwajeong; Galati, Lisa; Fantauzzi, John; Blinkhorn, Richard; Jennings, Timothy A.; Chaturvedi, Sudha; Judson, Marc A.
Abstract: We report a case of tonsillar histoplasmosis with hematogenous dissemination in a woman receiving infliximab for Crohn's disease. She also had a history of sarcoidosis. Due to the unusual location and confounding medical history, our case provided a diagnostic dilemma. Histoplasma infection was confirmed histologically, and the patient responded well to appropriate treatment.